An Experimental Study of Variable Oils Used in the Internal Combustion Engines Available In the Local Syrian Markets - حسن تمام (Latakia University Journal -Engineering Sciences Series, 2021)
The internal combustion engines can be considered as a thermal machine used for changing the thermal power to a mechanical power but this machine suffer of many high pressures and high straining through its different parts. as a result of the hard engine work situation , and high friction between the engine parts , the condition of the oils working lubrication have good relation and dependence with the engine specification correction with its load degree using condition and investment oiling circuit parameters also the oil kind used in the engine and its good ness. This paper presents a study of the specifications and characteristics of the oils used to lubricate the parts and parts of internal combustion engines with both diesel and spark ignition engines on the Syrian market, with a view to arriving at the selection of the best and most suitable oil for cars and weather conditions in the Syrian Arab Republic.